The emergence of goal pursuit: Mental contrasting connects future and reality - Kappes, A; Oettingen, G (Elsevier, 2014)
Mental contrasting of a desired future with the present reality strengthens the link between expectations and goal pursuit: The higher expectations of success, the more people engage in goal pursuit; the lower expectations of success, the more people let go or disengage from goal pursuit. In three studies, we tested if mental contrasting increases the link between expectations and goal pursuit by affecting the strength of mental associations between future and reality. We used lexical decision tasks to measure the strength of associations between future and reality for different domains of goal pursuit (i.e., interpersonal relations, achievement), and compared results in the mental contrasting condition to relevant control conditions (i.e., reverse contrasting and content control). In the mental contrasting condition but not in the control conditions emerged a strong link between expectations of success and the strength of associations between future and reality (Study 1, 2). The strength of associations between future and reality in turn mediated the link between expectations and self-reported as well as other-rated goal pursuit in the mental contrasting condition (Study 1, 2). Finally, the link between expectations and the strength of associations between future and reality in the mental contrasting condition vanished when the goal was attained (Study 3). Taken together, these results suggest that strength of future–reality associations are a mechanism specific to mental contrasting effects on goal pursuit.